Thoraco-lumbar section of vertebral column in light of various methods of measurements and its relation to the body height - Goździewski, Stanisław; Bujacz, Elżbieta; Marek, Janusz (Anthropological Review, 1976)
The authors have made measurements of thoraco-lumbar vertebral column and body height in a group of 776 students from University Medical School in Wrocław (332 males 444 females). Age range was 19-21 years, and most probably in this. age there is a termination of growth. The lenght of thoraco-lumbar vertebral. column as a whole and its parts is significantly larger in males, in both sexes the lenght is significantly, positively correlated with body height. Thoraco-lumbar index does not show intersexual differences. Comparing measurements of living persons with those taken on corpses and X-ray pictures by other investigators, the authors have arrived at a conclusion that measurements of thoracic segment are: more comparable than of lumbar one.